No evidence of metabolic cold adaptation in Drosophila melanogaster along a latitudinal gradient in Australia - O'Toole, Sinead (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScConsEcol)--Stellenbosch University, 2018.